2005
DOI: 10.1136/bjsm.2004.011767
|View full text |Cite
|
Sign up to set email alerts
|

Sweat rate and fluid turnover in American football players compared with runners in a hot and humid environment

Abstract: Objectives: To determine sweat rate (SwR) and fluid requirements for American footballers practicing in a hot, humid environment compared with cross country runners in the same conditions. Methods: Fifteen subjects, 10 footballers and five runners, participated. On the 4th and 8th day of preseason two a day practices, SwR during exercise was determined in both morning and afternoon practices/runs from the change in body mass adjusted for fluids consumed and urine produced. Unpaired t tests were used to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
72
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 27 publications
6
72
1
Order By: Relevance
“…Although daily sodium intake is likely adequate for most athletes in the United States, this may not hold true for football players who are known to lose up to 15 L of sweat per day during preseason training. 11 Investigators have reported on SwtNa + and sodium losses during training and games in European football (soccer) players 13,[16][17][18][19] and on SwtRs and sweat losses in endurance athletes, such as runners 3,20 ; however, few data on American football players are available. We have reported differences in SwtRs between LM and BK, but we have not studied the midsized players, such as linebackers, fullbacks, and quarterbacks (LB/QB).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although daily sodium intake is likely adequate for most athletes in the United States, this may not hold true for football players who are known to lose up to 15 L of sweat per day during preseason training. 11 Investigators have reported on SwtNa + and sodium losses during training and games in European football (soccer) players 13,[16][17][18][19] and on SwtRs and sweat losses in endurance athletes, such as runners 3,20 ; however, few data on American football players are available. We have reported differences in SwtRs between LM and BK, but we have not studied the midsized players, such as linebackers, fullbacks, and quarterbacks (LB/QB).…”
mentioning
confidence: 99%
“…Mean daily sweat losses of between 8 and 10 L/d were reported in a series of studies [3][4][5]9 involving both professional and collegiate football players. Using average sweat sodium concentrations (SwtNa + ) (approximately 50 mEq/ L), 13 calculated daily sodium losses in excess of 10 g/d have occurred in some of these players.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Average sweat rate during physical activity can vary from 0.5 L¡h -1 to more than 2.5 L¡h -1 [5,6] however these results portray a variety of exercise types, intensities and environmental conditions all of which affect sweat production. It is important to know that there are considerable variations in fluid loss between individuals in different activities and even within the same activity [22][23][24][25]. The sweat loss in the participants in the present study ranged from 0.7 L¡h -1 to 1.5 L¡h -1 ; factors such as genetic predisposition, heat acclimatization state and metabolic efficiency will influence sweat rates for each individual [6].…”
Section: Discussionmentioning
confidence: 99%
“…The hot-dry and warm-wet climates have a great influence on physiological systems, such as the nervous system, urinary system, digestive system, and immune system [7][8][9][10][11]. When working in the extreme climates, people would have a risk of experiencing the change of physiological parameters, such as increases of body temperature, heart rate, and sweat production [12][13][14][15][16][17]. The high temperature may reduce work efficiency and cause emotional instability, which will lead to the increase of industrial accident rates [18,19], so it is necessary to study the influencing factors on physiological parameters.…”
Section: Introductionmentioning
confidence: 99%